The Setswana speech rhythm of 6–7 year-old Setswana–English bilingual children. (June 2021) - Sebina, Boikanyego; Setter, Jane; Daller, Michael
Aims and objectives: This study investigates the acquisition of Setswana speech rhythm, considered to be typically syllable-timed, by early sequential Setswana–English bilingual children aged 6–7 years old growing up in Botswana, a country with a diglossic setting, where English is the dominant high-status language in educational and public contexts. For this group of children, taught full-time in English from the age of 3 years, the L2 becomes their dominant language through exposure to English-medium education. The aim was to ascertain if the prosodic patterns of Setswana spoken by the bilingual children are similar to those of the monolingual children or if English, considered to be stress-timed, has an effect on these prosodic features. Data and analysis: The speech rhythm patterns of 10 Setswana–English bilingual children were compared with those of 10 age-matched Setswana monolingual children educated in public schools for whom English is a learner language. The study primarily examines spontaneous speech from the telling of a wordless picture storybook, and utilises rhythm metrics nPVI-V and Varco V to examine the speech rhythm of the children. Findings: The results showed that the prosodic pattern of Setswana in the bilingual group diverged from that of the non-bilingual group. Originality: This is the first such study on speech rhythm in bilingual children in Setswana. Significance: The research provides evidence in this population of effects from English bilingualism on L1 Setswana speech prosody, and challenges the assumption that speech rhythm prosody is established early in life, especially when the language is a less marked, syllable-timed language like Setswana.